2023
DOI: 10.5498/wjp.v13.i6.361
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between depression, smartphone addiction, and sleep among Chinese engineering students during the COVID-19 pandemic

Abstract: BACKGROUND Existing research has demonstrated that depression is positively related to smartphone addiction, but the role of sleep has not been discussed thoroughly, especially among engineering undergraduates affected by the coronavirus disease 2019 pandemic. AIM To evaluate sleep as a mediator of the association between smartphone addiction and depression among engineering undergraduates. METHODS Using a multistage stratified random samplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…Similarly, studies conducted during the COVID-19 pandemic have also revealed correlation coefficients within the range of 0.20 to 0.50, indicating a similar relationship (e.g., W.-J. Gao et al, 2023;Lee et al, 2021;X. Yang et al, 2021).…”
Section: Discussionmentioning
confidence: 66%
“…Similarly, studies conducted during the COVID-19 pandemic have also revealed correlation coefficients within the range of 0.20 to 0.50, indicating a similar relationship (e.g., W.-J. Gao et al, 2023;Lee et al, 2021;X. Yang et al, 2021).…”
Section: Discussionmentioning
confidence: 66%
“…In addition, a significant but weak correlation between poor sleep quality and smartphone addiction was also evident in line with the literature findings (Achangwa, Ryu, Lee et al, 2022;Choi, 2015;Jo & Lee, 2019). In addition, recently Gao et al (Gao, Hu, Ji et al, 2023) also reported that sleep quality significantly mediated the effect of smartphone addiction and depression among university students. However, this research was conducted during the pandemic period, which is characterized by lockdowns, therefore the higher cumulative variances compared to ours might be attributed to this timeline.…”
Section: Discussionmentioning
confidence: 92%
“…According to existing studies, the prevalence of mobile phone addiction among Chinese college students ranges from 4.05 % to 63.58 % [ 48 , 49 ]. In this study, the prevalence was 10.94 % in Time 1 and increased to 13.73 % at Time 2.…”
Section: Discussionmentioning
confidence: 99%